Cioffari's Experiments in College Physics - Edmonds, Dean S.
For the full-year introductory physics course, calculus or non-calculus based, this complete laboratory text and workbook contains forty-four of the most popular college physics experiments. Each experiment includes detailed sections on theory, equipment, procedures, calculations, and questions. Available as a custom publishing option